Running after paradise : hope, survival, and activism in Brazil's Atlantic Forest - Scanlan Lyons, Colleen M., 1968- (Book collections on Project MUSE., 2022)
"This book looks at social-environmental activism in one of the world's most important and threatened tropical forests-Southern Bahia, Brazil. It explores what it means to be in and of a place through the lenses of history, environment, identity, class, and culture. It uncovers not only what separates people but also what brings them together as they struggle and strive to create their individual and collective paradise"--